Effects of EGR on combustion and emission characteristics of PODE/methanol RCCI mode at high load. (25th March 2023) - Liu, Junheng; Ma, Haoran; Wang, Lejian; Liang, Wenwen; Ji, Qian; Sun, Ping; Wang, Pan
Highlights: Combustion feature of PODE/methanol RCCI engine with EGR at high load are analyzed. EGR addition makes equivalent ratio and temperature field distributions more uniform. Reductions of HCO and OH radicals inhibit methanol spontaneous combustion and knock. Pilot injection strategy coupled with 18 %EGR can extend IMEP of RCCI mode to 1.22 MPa. The addition of EGR significantly reduces NOx emission without raising soot emission. Abstract: In order to extend the high-load operation range of polyoxymethylene dimethyl ethers (PODE)/methanol dual-fuel reactivity controlled compression ignition (RCCI) combustion mode, a numerical model of in-cylinder combustion was established by coupling PODE/methanol chemical reaction kinetics with CONVERGE software. And then the influence mechanism of exhaust gas recirculation (EGR) addition on in-cylinder combustion process, combustion stability and pollutant formation of the RCCI engine under high load and pilot injection strategy were investigated. The results show that with the increase of EGR ratio, the peak values of the first heat release formed by PODE pilot injection combustion and in-cylinder pressure decrease, the combustion start timing and CA50 phase are gradually delayed. While the peak value of the second heat release formed by PODE main injection combustion at low EGR ratio and the combustion duration remain unchanged. Meanwhile, as the EGR ratio increases from 0 to 30 %, the brake thermal efficiency (BTE) decreases from 46.54 % to 44.40 %. And the in-cylinder equivalent ratio and temperature field distributions become uniform, and both high-temperature region (above 1800 K) and NOx generation area are reduced, which decreases NOx emissions by 42.6 % without increasing soot emissions. The methanol mixture at squish zone is subjected to the high-temperature and high-pressure of pilot injection combustion, resulting in obvious pressure oscillation. While EGR addition decreases the generation of HCO and OH active radicals, ignition points and reaction rate, which effectively inhibits methanol spontaneous combustion and knock phenomenon, and decreases the ringing intensity from 2.82 MW/m 2 to 1.50 MW/m 2 . The pilot injection strategy coupled with 18 % EGR can extend the indicated mean effective pressure to 1.22 MPa. However, the load further extension is mainly limited by the sharp decline of BTE.